The gold content of mafic to felsic potassic magmas - Jia Chang; Andreas Audétat; Thomas Pettke (Nature Communications)
Abstract Many epithermal gold and gold-rich porphyry-type ore deposits are associated with potassic magmas. Hence, potassic magmas are commonly assumed to have been unusually Au-rich or to have contained high Au/Cu ratios. However, these hypotheses remain poorly tested. Here, we report Au concentrations and Au/Cu ratios in silicate melt inclusions analyzed in potassic rocks worldwide. The results suggest that mafic potassic magmas generally contain only 2‒7 ng/g Au, despite common sulfide exhaustion during partial mantle melting. Both the absolute Au concentrations and Au/Cu ratios are comparable to those of mafic calc-alkaline magmas, and they vary little during subsequent magma differentiation because magmatic sulfide precipitation is strongly dominated by monosulfide solid solution that is relatively poor in Au and Cu. We thus suggest that the close association of Au-rich deposits with potassic magmas is not due to Au enrichment in the magma, but rather due to selective Au precipitation at the hydrothermal stage.